Desafios para a implantação de um processo de mensuração de impactos gerados por negócios sociais ligados à economia criativa no estado do Rio de Janeiro - Pereira, João Batista Machado (2021)
This dissertation seeks to investigate impact measurement processes produced by social businesses linked to creative economy in the state of Rio de Janeiro. Its contribution is to provide empirical evidence regarding the challenges, limitations and specificities for the application of the classic mechanisms for measuring impacts in these businesses. To this end, a case study was conducted, based on a social business located in Rio de Janeiro. This research adopts an interpretative approach, assuming as its primary data collection tool in-depth interviews with the representative of this social business and with actors of the social impact ecosystem to which this business belongs. Through discourse analysis of the interviewees, this research identified that factors inherent to the process and inherent to the context influence the implementation of classic mechanisms for measuring impacts on social businesses linked to creative economy in the state of Rio de Janeiro. Factors inherent to the process are associated with the impact measurement process in its implementation phases: initiation, growth and maturity. The difficulties in defining the motivation to implement a measurement process and the lack of resources necessary to implement and maintain this process were characterized as offenders. The factors inherent to the context are related to the environment where this process exists, being those associated with culture, information technology and government. The latter appear as a little inducing agent in the formation of local impact business ecosystems due to the absence of instruments, incentives and concrete policies that recognize the value of this type of business. This research also identified that the classic impact measurement mechanisms don’t need any particular adjustment to become suitable for use on social businesses. Finally, it became evident that the informal culture present in Rio de Janeiro, in the country and in this ecosystem in particular is a factor that hinders measurement processes, while information technology presents itself in due course as an ally in overcoming various difficulties